High Knowledge On Dengue But Low Preventive Practices Among Residents In A Low Cost Flat In Ampang, Selangor - Rosmawati, Mat Ali; Hamid Jan, Jan Mohamed; Norfarhana, Ramly (2016)
Dengue incidence has grown dramatically in recent decades and become global, especially in the urban area. Ministry of Health (MOH) Malaysia reported that the number of dengue cases since January 2014 until Jun 2014 was 38, 411 cases which was higher compared to the number reported in year 2013 (10, 910 cases). The objective of the study was to determine the knowledge and preventive practices of dengue among residents in Flat Pandan Indah, Ampang Selangor. A cross sectional study design with convenience sampling method was adopted in this study. A total of 298 respondents living in Flat Pandan Indah were recruited based on the inclusion criteria. A validated questionnaire that measures knowledge and preventive practices of dengue was completed by respondents. More than half of the respondents had scored 61.7% good knowledge regarding dengue; however, there were 50.3% of the respondents had a limited extent of dengue practice. Almost all of the respondents (95.6%) reported that television or radio as the main source for information on dengue. . The common preventive measures used by the respondents were cleaning the house (n=148, 49.7%), eliminating standing water around the house (n=123, 41.3%) and covers water containers in the home (n=120, 40.3%). There was no correlation between dengue knowledge and preventive practices score (r=0.093), (p = 0.109). The study reveals that the majority of the respondents had good knowledge regarding dengue but the practices to prevent dengue are poor. Thus, health education program focusing on dengue prevention practices should be done on the community members in the future.